Trauma cinema : documenting incest and the Holocaust - Walker, Janet, 1955- (University of California Press, 2005)
Trauma Cinema focuses on a new breed of documentary films and videos that adopt catastrophe as their subject matter and trauma as their aesthetic. Incorporating oral testimony, home-movie footage, and documentary reenactment, these documentaries express the havoc trauma wreaks on history and memory. Janet Walker uses incest and the Holocaust as a double thematic focus and fiction films as a point of comparison. Her astute and original examination consid.